Tomato genotype response to organic and synthetic fertilizers - Sunday Ayodele Ige; Aboyeji Christopher; Akodu Faith; Stephen Abolusoro; Charity Aremu; Bashir Omolaran Bello; Adebiyi Ojo; Adeniyi Victoria; Chijioke Favour (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: The study investigated how selected tomato genotypes performed with combined applications of cocoa pod (CP) + poultry manure (PM), kola nut pod (KP) + poultry manure (PM), and NPK fertilizer, focusing on fruit yield, mineral content, and vitamin composition.